Entrepreneurship Behaviour In The Millennial Generation At Pondok Pesantren Darull Mutaqiuen 1 Sepatan Tangerang - Yuwono Priyanto; Ela Suryani; Jeannet Kunta Adjie (Pelopor Publikasi Akademika, 2023)
To open a mindset, form a character, instead a sense of independence and cooperation in students and students, and give entrepreneurial material at the Darul Muttaquien 1 Islamic Boarding School, researchers provided material on behaviour, or manners that needed to be built in establishing entrepreneurship. This information is being made available to students and students at the Darull Mutaqien 1 Islamic boarding school so that they can participate in creating an entrepreneurial venture and meet the challenges of the increasingly competitive working world. The character traits that should be developed to succeed as an entrepreneur like integrity, perseverance, self-assurance, responsibility, and, perhaps most importantly, the willingness to take risks. To become an entrepreneur or to start a business, a person must have the courage to take risks to compete and spread the gospel of entrepreneurship in the community.